Differential gene expression in peripheral blood mononuclear cells from children immunized with inactivated influenza vaccine. Issue 8 (2nd August 2020) - Alcorn, John F.; Avula, Raghunandan; Chakka, Anish B.; Schwarzmann, William E.; Nowalk, Mary Patricia; Lin, Chyongchiou Jeng; Ortiz, Marianna A.; Horne, William T.; Chandran, Uma R.; Nagg, Jennifer P.; Zimmerman, Richard K.; Cole, Kelly S.; et al.
ABSTRACT: The human immune response to inactivated influenza vaccine is dynamic and impacted by age and preexisting immunity. Our goal was to identify postvaccination transcriptomic changes in peripheral blood mononuclear cells from children. Blood samples were obtained before and at 3 or 7 days postvaccination with 2016–2017 quadrivalent inactivated influenza vaccine and RNA sequencing was performed. There were 1, 466 differentially expressed genes (DEGs) for the Day 0–Day 3 group and 513 DEGs for the Day 0–Day 7 group. Thirty-three genes were common between the two groups. The majority of the transcriptomic changes at Day 3 represented innate inflammation and apoptosis pathways. Day 7 DEGs were characterized by activation of cellular processes, including the regulation of cytoskeleton, junctions, and metabolism, and increased expression of immunoglobulin genes. DEGs at Day 3 were compared between older and younger children revealing increased inflammatory gene expression in the older group. Vaccine history in the year prior to the study was characterized by robust DEGs at Day 3 with decreased phagosome and dendritic cell maturation in those who had been vaccinated in the previous year. PBMC responses to inactivated influenza vaccination in children differed significantly by the timing of sampling, patient age, and vaccine history. These data provide insight into the expected molecular pathways to be temporally altered by influenza vaccination in children.